2019
DOI: 10.2220/biomedres.40.57
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in basal lamina fenestrations in rat intestinal villous epithelium under high-fat diet condition

Abstract: The basal lamina of the villous epithelium in the small intestine has numerous fenestrations, which are produced by leukocytes for their intraepithelial migration. We previously showed that these fenestrations change due to the dynamics of migrating leukocytes in response to dietary conditions and suggested the possibility that this change is related to the regulation of the absorption of large-sized nutrients such as chylomicrons. The present study was, thus, designed to investigate structural changes in basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…villi provide an important pathway for large nutrients, such as chylomicrons, to be released from the epithelial side to the space of the lamina propria (Azumi et al 2018). Moreover, we also previously demonstrated that the number of free cells passing through the fenestrations increased in the upper jejunum after feeding a high-fat diet, and the size of the fenestrations in this region also increased (Morita et al 2019). Because it is probable that the size and number of fenestrations are related to the efficiency of fat absorption, we strongly hypothesize that the increase in fenestration area may facilitate the passage of large substances such as chylomicrons.…”
Section: Change In the Number Of Migrating Free Cellsmentioning
confidence: 61%
See 3 more Smart Citations
“…villi provide an important pathway for large nutrients, such as chylomicrons, to be released from the epithelial side to the space of the lamina propria (Azumi et al 2018). Moreover, we also previously demonstrated that the number of free cells passing through the fenestrations increased in the upper jejunum after feeding a high-fat diet, and the size of the fenestrations in this region also increased (Morita et al 2019). Because it is probable that the size and number of fenestrations are related to the efficiency of fat absorption, we strongly hypothesize that the increase in fenestration area may facilitate the passage of large substances such as chylomicrons.…”
Section: Change In the Number Of Migrating Free Cellsmentioning
confidence: 61%
“…We also suggested that basal lamina fenestrations are changed according to the dynamics of migrating leukocytes under certain dietary conditions. To further clarify the role of fenestrations in lipid absorption, we investigated the dynamics of basal lamina fenestrations under high-fat diet condition (Morita et al 2019). We showed that basal lamina fenestrations provide important pathways for the release of chylomicrons from the epithelial side to the side of the lamina propria and proposed that dynamic changes in basal lamina fenestration may play an important role in increasing or decreasing the efficiency of lipid absorption (Morita et al 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations